The Significance of the Concept of Intersectionality for Social Pathology: Epistemological and Methodological Aspects - Petkovska, Sanja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
The aim of the paper is to consider the importance of intersectionality as an innovative theoretical and methodological tool for conceptualizing the social differences in the field of social pathology. In order to realize the goal set, we first approach the definition of intersectionality and its delimitation in relation to related concepts, while clarifying our own understanding of the concept, which we base on material directions within the approach of diversity politics and critical race theory. Unlike modern sociological understandings, contemporary studies of social differences theoretically rely on more complex approaches, such as constructivist interactionism, phenomenology, post-Marxism, gender studies, post-colonial studies, and critical theories of society, which focus on identity and subjectivity. The materialistic aspect of the critical approach and issues related to policies of distribution are mostly neglected, amid the dominance of the postmodernist culture of thinking, which often manifests itself as imprecise and unfounded. The initial impulse for writing this paper is precisely the effort to reanimate that repressed, material dimension. Then, the paper shows the advantages of using the intersectional approach in the research of critical analysis of public policies and critical criminology, so that the focus in the final part of the paper is directed to specific methodological topics and problems in the study of which the concept of intersectionality has proven to be important and necessary.